MAKNA FILOSOFIS DALAM TRADISI TEDAK SITEN SEBAGAI CERMINAN IDENTITAS BUDAYA JAWA - Arif Saefudin; Fitria Nungki Anjani (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2026)
This study aims to examine and reveal the philosophical meaning contained in the Tedak Siten traditional ceremony, a Javanese tradition that symbolises an important process in children's lives. The preservation of this traditional culture is very important to maintain the cultural identity of the archipelago, which is rich in noble values. This study employs a descriptive qualitative method with an ethnographic approach to explore the symbolic meanings and philosophical values implied in each stage of the Tedak Siten ceremony. Data was collected through in-depth interviews with tradition practitioners and traditional leaders, as well as direct observations of the ceremony's implementation in several regions in Central Java and Yogyakarta. The research findings reveal that Tedak Siten is not merely a rite of passage in a child's development but is also imbued with values of community, spirituality, and moral teachings passed down through generations. This ceremony teaches the importance of individual readiness in facing life with the support of the community and the blessing of the universe. Through the preservation of the Tedak Siten tradition, the cultural values of the Nusantara remain alive and relevant for future generations. From a scientific paradigm perspective, this research emphasises the study of cultural philosophy. Through an ethnographic approach, this research reveals the philosophical meanings inherent in the symbols and rituals of the ceremony, rather than merely reconstructing its historical aspects. Thus, the main focus of this research is the exploration of the philosophical values contained in traditional cultural practices.